Carbon Disclosure, Managerial Ownership, Leverage, And Company Value - Hartanti, Arifika Sekaringtias; Khairunnisa, Khairunnisa; Wahyuni, Dhian (UNIVERSITAS PAKUAN, 2024)
This study intends to ascertain the impact of management ownership, leverage, and carbon disclosure on business value in companies in the logistics and transportation sector listed on the Indonesia Stock Exchange for 2016–2022. The carbon disclosure variable is calculated using GRI 305 proxy, managerial ownership is using MO proxy, Debt to Assets Ratio (DAR) as a proxy for leverage, and company value using Tobin's Q proxy. The research population is a company in the transportation and logistics sector listed on the Indonesia Stock Exchange for 2016-2022. Six different companies served as the study's samples, and there were a total of 42 observations. Purposive sampling served for selecting the study's sample. As a result, the variables of carbon disclosure, managerial ownership, and leverage simultaneously affect firm value. Partially, carbon disclosure and managerial ownership have a significant negative impact on company value. Leverage does not, however, significantly increase the value of a corporation.